ANALYSIS OF FACTORS RELATED TO THE EVENT OF OSTEOPOROSIS IN WOMEN - Rachmawaty M. Noer; Mira Agusthia; Jaspirgon Jaspirgon (Universitas Bengkulu, 2020)
Awal Bros Hospital Batam in the last 2 years namely in 2018 there were 14 women and in 2019 there were 23 women who had osteoporosis.Data obtained in the last 2 years, namely in 2018 there were 20 women and in 2019 there were 31 women with osteoporosis. From the information above, there are still many women affected by osteoporosis, but still do not know about the factors that cause osteoporosis itself. This study aims to determine the factors related to the occurrence of osteoporosis in women in Embung Fatimah Regional Hospital Batam Bintan in 2019 on February 27 to March 11, 2020. The design of this study is descriptive quantitative with cross sectional approach with the sampling method in this study. is total sampling. The sample in this study consisted of women with osteoporosis at the Embung Fatimah Regional Hospital in Batam City amounting to 31 people and the data were analyzed using the chi-square test. The results showed that there was a relationship between respondent's knowledge of the incidence of osteoporosis in Embung Fatimah Regional Hospital in Batam City, there was a relationship between respondents 'attitudes toward osteoporosis in Embung Fatimah Regional Hospital in Batam City, there was a relationship between respondents' lifestyle on the incidence of osteoporosis in Embung Fatimah Regional Hospital in Batam City. From the results of the analysis, the determinant coefficient value (Adjusted R Square) = 0.312 means that 31.2% of knowledge, attitude and lifestyle factors can be explained about the incidence of osteoporosis.